Addressing the ongoing friction between anecdotal and evidence-based teachings in osteopathic education in Europe. Issue 3 (July 2018) - Sposato, Niklas; Shaw, Robert; Bjerså, Kristofer
Abstract: Despite a growing interest in research and the implementation of standards for osteopathic education and practice in Europe, the inter-professional dialogue remains insubstantial. This article calls attention to the continuous challenges of reconciling anecdotal and evidence-based perspectives and offers suggestions on how to address these areas further.